Sonographic and Clinical Features of Upper Extremity Deep Venous Thrombosis in Critical Care Patients - Michael Blaivas; Konstantinos Stefanidis; Serafim Nanas; John Poularas; Mitchell Wachtel; Rubin Cohen; Dimitrios Karakitsos (Critical Care Research and Practice)
Background-Aim. Upper extremity deep vein thrombosis (UEDVT) is an increasingly recognized problem in the critically ill. We sought to identify the prevalence of and risk factors for UEDVT, and to characterize sonographically detected thrombi in the critical care setting. Patients and Methods. Three hundred and twenty patients receiving a subclavian or internal jugular central venous catheter (CVC) were included. When an UEDVT was detected, therapeutic anticoagulation was started. Additionally, a standardized ultrasound scan was performed to detect the extent of the thrombus. Images were interpreted offline by two independent readers. Results. Thirty-six (11.25%) patients had UEDVT and a complete scan was performed. One (2.7%) of these patients died, and 2 had pulmonary embolism (5.5%). Risk factors associated with UEDVT were presence of CVC [(odds ratio (OR) 2.716, P=0.007)], malignancy (OR 1.483, P=0.036), total parenteral nutrition (OR 1.399, P=0.035), hypercoagulable state (OR 1.284, P=0.045), and obesity (OR 1.191, P=0.049). Eight thrombi were chronic, and 28 were acute. We describe a new sonographic sign which characterized acute thrombosis: a double hyperechoic line at the interface between the thrombus and the venous wall; but its clinical significance remains to be defined. Conclusion. Presence of CVC was a strong predictor for the development of UEDVT in a cohort of critical care patients; however, the rate of subsequent PE and related mortality was low.